Gaya Kepemimpinan Transformasional melalui Manajemen SDM dalam Penguatan Ekonomi Perbankan Syariah - Budiarto, Irvan Dian (Idarotuna : Journal of Administrative Science, 2024)
Transformational leadership plays a key role in making Islamic banking more appealing and competitive, particularly when it comes to overcoming the obstacles posed by the digital financial sector. The purpose of this study is to examine how sharia values are applied in banking operations, innovation is promoted, employee competency is maximized, and leadership is changed in HR. The primary method used in this study to examine the theory and application of transformational leadership in the Islamic banking industry is a qualitative approach with a literature review. According to the study's findings, transformational leadership helps to fortify an Islamically oriented workplace culture, boost employee motivation, and create a dynamic work environment. Additionally, competency-based hiring, ongoing training, and equitable pay are all components of HR management methods that help organizations become more productive and adapt to changes in the industry. It has been demonstrated that sharia banking that employs transformational leadership is more inventive, robust to economic volatility, and capable of enhancing societal financial inclusivity. As a result, transformational leadership is crucial for sharia-based economic stability and growth in addition to being essential for company sustainability.